Identyfikacja i ocena kultury organizacyjnej na przykładzie Powiatowej Stacji Sanitarno-Epidemiologicznej w Nowym Sączu - Guzik, Grzegorz (My University, 2012)
Podstawą funkcjonowania każdej organizacji i osiągania założonych celów są pracownicy. To oni kształtują wizerunek, tworzą kulturę organizacyjną i renomę firmy w otoczeniu. Ich kompetencje, wiedza i umiejętności decydują o efektywności i skuteczności działania danej organizacji. Dzięki ich pracy powstają produkty i usługi zaspokajające potrzeby społeczne a tym samym postęp organizacyjny.

Employees are the foundation of performing and achieving determined objectives. They are the ones who shape the image, create organizational culture and repute of the company in the environment. Their competences, knowledge and abilities determine the efectiveness and results of actions given company. By dint of their work products and services are created in order to fulfill social needs and therefore organizational progress.
Identification and assessment of organizational culture on the example of the Epidemical and Sanitary Station in Nowy Sącz
Keywords: zarządzanie przedsiębiorstwem; kultura organizacji pracy; identyfikacja z przedsiębiorstwem; management; organizational culture of work; identification with company